Adverse Events Among Plateletpheresis Donors in a Tertiary Care Hospital at Dhaka, Bangladesh - Biswas, Daanish Arefin; Wasim, Md; Bhuiyan, Hasiba Akhter; Haque, Md Rafiqul; Nur, Jannatun; Akhi, Tonima Taji; Rashid Un Nabi, Quazi Md (Sir Salimullah Medical College Journal, 2023)
Introduction: The rising demand for platelet transfusions among patients has increased the usage of automated blood collections. Many of the same reactions and injuries are found with pooled platelets received from whole blood donation, although notable differences exist. Objective: To study the adverse events (AEs) during plateletpheresis procedures in a tertiary care hospital and plateletpheresis procedure session profiles. Materials and Methods: This retrospective study was conducted from January 2021 to December 2021 by analyzing records of two-hundred and thirteen (213) plateletpheresis procedures done in transfusion medicine department. All the donors were male. All adverse effects were recorded and noted in the registrar. Results: A total of 13 (Thirteen) AEs were noted, of which 08 (61.53%) events were associated with donors, 03 (23.07 %) were owed to a fault in the kit/equipment, and 02 (15.38 %) were due to technical faults. Donor-related AEs included hematoma (23.07%), vasovagal (23.07%), and perioral tingling sensation (15.38%). Technique-related AEs were 23.07%, and faulty kit/equipment-related AEs were 15.38%. Conclusion: Apheresis donations performed on apheresis machines are safe. Careful donor selection, well-trained expert technical personnel, and supervision of experienced transfusion medicine specialists will make the donor’s experience more pleasant. Sir Salimullah Med Coll J 2023; 31: 67-72